Pengaruh Literasi Keuangan dan Penggunaan E-Wallet terhadap Financial Behavior Mahasiswa di Kota Tasikmalaya - Nazia Sariul Wafa (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
This research aimed to examine how financial literacy and the use of digital payment systems impact students' financial behavior in the Tasikmalaya area. Although digital wallets are widely used for transactions, many students do not realize that this ease of access can shape their financial habits. Often, e-wallets are seen purely as convenient tools, without acknowledging their influence on spending patterns and money management. A quantitative method was employed, with data gathered via questionnaires distributed to 140 student respondents. The findings show that financial literacy significantly affects financial behavior on its own, while e-wallet usage does not have a notable individual impact. Nevertheless, when both variables are analyzed simultaneously, they significantly influence financial behavior. These outcomes are consistent with the Theory of Planned Behavior, which explains that personal attitudes, control over behavior, and habits collectively contribute to financial decisions.Based on these results, the study suggests that improving financial literacy is crucial so that students can make more informed decisions and manage their finances wisely when using digital wallets.